Estimation of Hepcidin and Sexual Hormones Levels in Patients with Atherosclerosis in Al-Najaf City / Iraq - Furqan Moein Auda; Basim M. Ali; Maha Al-Andaleb; Mansoor K. Abidali; Shaymaa Dhyaa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Atherosclerosis is a serious disease that threatens the lives of both male and female. The risk of this diseaseincreases with age. In the current study, we attempted to estimate the most important indicators affected byheart disease, such as Hepcidin , iron, and sex hormones , 40 men and 20 women participated in this work,with age in range (45-75) years, all of them suffering from atherosclerosis . on the other hand, 15 healthymen and 15 healthy women participated as a control group The results have shown a significant change inthe level of Hepcidin among the patients compared to the control group. Additionally, the results of the studyalso proved that men with atherosclerosis suffer from a deficiency of the sexual hormone(testosterone).Remarkably , the present study has reported that patients with atherosclerosis are more susceptible tooxidative stress due to an increase in iron level on the other hand, men with atherosclerosis are more probableto have sexual dysfunction with age.